The Use of Structures and Functions of Lexical Bundles in Conversation Texts in Bahasa Inggris Textbook Published By Kemendikbud - Inaroh, Inaroh; Faridi, Abdurrachman; Wuli Fitriati, Sri (English Education Journal, 2021)
This study investigated the use of structures of lexical bundles, functions of lexical bundles, and the relationship between structures and functions of bundles in conversation texts. For the purposes of the study, the BahasaInggris textbook, published by the Ministry of Education and Culture(2018), was chosen to be analyzed. In the process of collecting the data, a set of tables was used. The first table was used to collect data to analyze structures of lexical bundles based on Biber's (2006) theory. The second table was used to collect data regarding Biber and Conrad's (2005) theory for functions of lexical bundles. Procedures for analyzing data consisted of steps, including reading, categorizing, and analyzing. This study revealed that, firstly, personal pronoun + lexical VP (e.g. we are going to) identified as the most frequent structure of bundle appeared in the conversation texts.Secondly, stance expression had a high proportion of the most recurring function of the bundle. They are used for expressing desire, intention, ability, obligation, and showing certain and uncertain feelings. Moreover, there were relationships between the functions of bundles with particular structures. In conclusion, improving the teaching quality can be built based on the appropriateness of the textbook. The teacher needs to pay attention to the English book that they will use, especially those that provide enough materials for enhancing students’ formulaic competence